Prebiotics – an added benefit of some fibre types. Issue 1 (1st February 2019) - Lockyer, S.; Stanner, S.
Abstract: Prebiotics are food components that are selectively used by gut bacteria, conferring a health benefit, most notably stimulating the growth of bifidobacteria. Accepted prebiotics at present are the fibre types galacto‐oligosaccharides, fructo‐oligosaccharides and inulin, some forms of which occur naturally in foods such as pulses, grains, fruit and vegetables. Prebiotics can also be isolated and produced commercially for use as functional ingredients and supplements. The aim of this paper is to provide an overview of the place of prebiotics in a healthy, balanced diet, to explore potential health effects, particularly in relation to gut health, and to consider whether there are implications of consuming a diet low in prebiotics. Dietary fibre is important for health, with high‐fibre diets reducing risk of several chronic diseases, via its effects on bowel function, gut microbiota, and cholesterol and glycaemic levels. The prebiotic effects of some fibre types may contribute to these effects. Evidence from supplementation studies carried out in humans suggests that consumption of prebiotics may confer an array of health benefits such as cholesterol lowering, relief of symptoms of gastrointestinal disorders, increased satiety and immunomodulatory effects, though more studies are needed. Findings from observational and intervention studies indicate that exclusion diets, such as low‐carbohydrate, gluten‐free and the low Fermentable Oligosaccharides, Disaccharides, Monosaccharides and Polyols diet, result in changes to the gut microbiota such as reduced abundance of Bifidobacterium and Lactobacillus species, though whether or not there are any long‐term health implications remains unknown. Studies investigating whether prebiotic supplements may be useful in conjunction with such diets (when these are required for medical reasons) to help restore levels of bacteria that are considered to be beneficial, are warranted. Overall, there is a need to promote high‐fibre foods across the UK population as intakes currently fall well below recommendations.